2005
DOI: 10.1021/jf048439o
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Spectroscopic Based Studies of the Metabolism of Black Tea Polyphenols in Humans

Abstract: Epidemiological studies indicate that a high intake of flavonoids is associated with an improved health status. Tea is one of the most abundant sources of flavonoids in the human diet. The bioavailability and biotransformation of tea flavonoids are, however, not clearly understood. The aim of the present study was to investigate the metabolism of black tea via a nonspecific screening method. (1)H nuclear magnetic resonance (NMR) spectroscopy was used to obtain nonselective profiles of urine samples collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 34 publications
6
97
1
Order By: Relevance
“…Non-transformed metabolites are excreted in urine and feces. Hippurate is a known urinary excretion product associated with consumption of black tea (54,55). Gavaghan et al (56) have reported dietary effects on the urinary excretion of hippuric acid and chlorogenic acid metabolites in a genetically homogeneous population of rats maintained under identical conditions and have pointed out the possible influence of gut microflora on the metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Non-transformed metabolites are excreted in urine and feces. Hippurate is a known urinary excretion product associated with consumption of black tea (54,55). Gavaghan et al (56) have reported dietary effects on the urinary excretion of hippuric acid and chlorogenic acid metabolites in a genetically homogeneous population of rats maintained under identical conditions and have pointed out the possible influence of gut microflora on the metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Within the field of nutrition, NMR-based metabonomics is slowly emerging as a tool for elucidating how diet elicits changes in the metabolite profile. Applications of NMRbased metabonomics on blood plasma and urine samples for elucidating the biochemical effects of dietary bioactive compounds such as epicatechin [14], isoflavones [15], chamomile [16] and tea phenols [17] have been reported. In addition, it has also been demonstrated that NMR-based metabonomics is valuable for elucidating how wholegrain and cereal fractions alter the urine and plasma metabolite profile of pigs [18] and rats [19].…”
Section: Introductionmentioning
confidence: 99%
“…Hippurate has also been reported as a metabolic end product of plant phenols and flavonoids by the gut microflora (Daykin et al 2005;Mulder et al 2005;Nicholson et al 2005;Van Dorsten et al 2006;Wang et al 2005) and hence, it can also be speculated that hippurate is partially a metabolic signature by the gut microflora of the subjects participating in the present study.…”
Section: Associations Between Dietary Fibre and Human Urinary Metabolmentioning
confidence: 67%